Mapping instruments for assessing and stratifying frailty among community-dwelling older people: a scoping review - Luiz Eduardo Lima Andrade; Beatriz Souza de Albuquerque Cacique New York; Rafaella Silva dos Santos Aguiar Gonçalves; Sabrina Gabrielle Gomes Fernandes; Álvaro Campos Cavalcanti Maciel (BMJ Open)
Objective To map in the current literature instruments for the assessment and stratification of frailty in community-dwelling older people, as well as to analyse them from the perspective of the Brazilian context.Design Scoping review.Study selection The selection of studies took place between March and April 2020. Includes electronic databases: Medline, Latin American and Caribbean Literature in Health Sciences, Scopus, Web of Science and Cumulative Index of Nursing and Literature Health Alliance, in addition to searching grey literature.Data extraction A data extraction spreadsheet was created to collect the main information from the studies involved, from the title to the type of assessment and stratification of frailty.Results In summary, 17 frailty assessment and stratification instruments applicable to community-dwelling older people were identified. Among these, the frailty phenotype of Fried et al was the instrument most present in the studies (45.5%). The physical domain was present in all the instruments analysed, while the social, psychological and environmental domains were present in only 10 instruments.Conclusions This review serves as a guideline for primary healthcare professionals, showing 17 instruments applicable to the context of the community-dwelling older people, pointing out advantages and disadvantages that influence the decision of the instrument to be used. Furthermore, this scoping review was a guide for further studies carried out by the same authors, which aim to compare instruments.